Scientific-Basic Approaches to Improving Graphic Literacy among Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the role of drawing in modern technological progress, its importance in engineering, architecture and production processes, its role in the educational process and its contribution to the development of the thinking of the younger generation. It also analyzes the close relationship of drawing with other disciplines and its practical importance in professional fields.